Open access journal publishing in the Nordic countries - Björk, Bo-Christer (Learned Publishing, 2019)
The number of open access (OA) journals and their share of all scholarly journals are usually estimated based on indexing in the Directory of Open Access Journals (DOAJ). DOAJ's coverage of OA journals from different regions of the world is, however, far from complete, particularly of journals publishing in languages other than English. Using alternative data sources for identification and manual verification, 437 scholarly OA journals published in the five Nordic countries (Denmark, Finland, Iceland, Norway, and Sweden) were identified, and some key characteristics were studied. Of these, only 184 were indexed in DOAJ. A vast majority of the journals was published by scholarly societies or universities. Social sciences and humanities dominated as topics, and few journals charge authors. National or university-specific OJS portals have played a major role in enabling OA publishing. Around a third of the Nordic scholarly journals are currently OA. Peer reviewed